Domestic politics, international bargaining and China's territorial disputes - Chung, Chien-Peng (London : RoutledgeCurzon, 2004)
An analysis of China's territorial disputes, exploring the successes and failures of negotiations that have taken place between China and its neighbors, namely India, Japan, Russia, and countries in Southeast Asia.
The two-level game hypothesis -- The Diaoyu/Tiaoyutai/Senkaku Islands dispute -- The Zhenbao/Chenpao/Damansky Islands dispute -- The McMahon Line/Aksai Chin dispute -- Beyond two-level games? -- Testing the propositions of the two-level game hypothesis.
Includes bibliographical references : (p. [175]-211) and index.
Keywords: China -- Foreign relations -- 1949-; China -- Boundaries; China -- Politics and government -- 1949-